Lineage-specific co-evolution of the Egf receptor/ligand signaling system - Laisney, Juliette AGC (BioMed Central, 2010)
BACKGROUND: The epidermal growth factor receptor (Egfr) with its numerous ligands has fundamental roles in development, cell differentiation and physiology. Dysfunction of the receptor-ligand system contributes to many human malignancies. Consistent with such various tasks, the Egfr gene family has expanded during vertebrate evolution as a consequence of several rounds of whole genome duplication. Of particular interest is the effect of the fish-specific whole genome duplication (FSGD) on the ligand-receptor system, as it has supplied this largest group of vertebrates with additional opportunities for sub- and/or neofunctionalization in this signaling system. RESULTS: We identified the predicted components of the Egf receptor-ligand signaling system in teleost fishes (medaka, platyfish, stickleback, pufferfishes and zebrafish). We found two duplicated egfr genes, egfra and egfrb, in all available teleost genomes. Surprisingly only one copy for each of the seven Egfr ligands could be identified in most fishes, with zebrafish hbegf being the only exception. Special focus was put on medaka, for which we more closely investigated all Egf receptors and Egfr ligands. The different expression patterns of egfra, egfrb and their ligands in medaka tissues and embryo stages suggest differences in role and function. Preferential co-expression of different subsets of Egfr ligands corroborates the possible subfunctionalization and specialization of the two receptors in adult tissues. Bioinformatic analyses of the ligand-receptor interface between Egfr and its ligands show a very weak evolutionary conservation within this region. Using in vitro analyses of medaka Egfra, we could show that this receptor is only activated by medaka ligands, but not by human EGF. Altogether, our data suggest a lineage-specific Egfr/Egfr ligand co-evolution. CONCLUSIONS: Our data indicate that medaka Egfr signaling occurs via its two copies, Egfra and Egfrb, each of them being preferentially coexpressed with different subsets of Egfr ligands. This fish-specific occurrence of Egf receptor specialization offers unique opportunities to study the functions of different Egf receptor-ligand combinations and their biological outputs in vertebrates. Furthermore, our results strongly support the use of homologous ligands in future studies, as sufficient cross-specificity is very unlikely for this ligand/receptor system.